Strongylidium koreanum n. sp. (Protozoa: Ciliophora), a new soil species from South Korea - Chae, Kyu-Seok; Park, Kyung-Min; Min, Gi-Sik (Zootaxa, 2023)
Strongylidium koreanum n. sp., a new soil ciliate from Jeju Island, South Korea, is described based on live observations, protargol impregnation, and molecular analysis of the 18S rRNA gene sequence. It is characterized by the following morphological features: cell outline more or less fusiform, posterior end broader than anterior end; grayish under low magnification; cortical granules absent; 23–32 adoral membranelles; three enlarged frontal cirri; buccal cirrus and postoral ventral cirrus present; 27–42 left and 15–28 right ventral cirri; 23–36 left and 30–46 right marginal cirri; three dorsal kineties; three caudal cirri; and two macronuclear nodules with two or three micronuclei. Phylogenetic analyses show that Strongylidium is monophyletic.